High temperature performance of SBS modified bio-asphalt. (30th July 2017) - Zhang, Ran; Wang, Hainian; Gao, Junfeng; You, Zhanping; Yang, Xu
Highlights: A new sustainable and environmentally-friendly pavement material, SBS modified bio-asphalt, was developed. High temperature performance of SBS modified bio-asphalt was studied. The mixing and compaction temperatures of SBS modified bio-asphalts were determined. SBS modified bio-asphalt has better or equal high temperature performances than base binder. Abstract: Crude oil-based asphalt supplies are shrinking while its demand is increasing rapidly; this, in turn, has led to an increase in the price of asphalt binder. As the price of asphalt increases, seeking for alternative and renewable binder resources, such as bio-asphalt, has become a hot research topic. However, the high temperature performances of bio-asphalt are unsatisfactory according to many previous studies. This study aims to enhance the high temperature performance of bio-asphalt by adding SBS into the matrix asphalt. Five types of SBS modified bio-asphalts were studied. Studies included their viscosity, anti-rutting performance and temperature sensitivity through the rotational viscometer (RV) and dynamic shear rheometer (DSR). Among them, SBS dosage was 1% of SBS modified bio-asphalt and the 50 penetration grade binder was applied as the base binder. The bio-oil contents for the five types of binders were 0%, 5%, 10%, 15% and 20% by weight of the SBS modified bio-asphalt. It was found that SBS modified bio-asphalt had higher viscosity than the base binder to some degree, and the effect of bio-oil on SBS bio-binder viscosity was small when the bio-oil content and testing temperature were high. The mixing and compaction temperatures of SBS modified bio-asphalt were about the same as those of the 50# base binder when the bio-oil content was more than 10%. Before RTFO testing, the SBS bio-binder had more viscous characteristics and a lower anti-rutting performance, but was not significantly different from that of the base binder. However, an opposite trend was observed after the RTFO test. Meanwhile, SBS bio-binder was less sensitive to temperature than the base binder and such sensitivity decreased with the increase in bio-oil content before RTFO. After RTFO, the temperature sensitivity of the SBS bio-binder was still lower than that of the 50# base binder when bio-oil content was less than 20%, and grew with the increase in bio-oil content.